The Southeastern Librarian, Vol.33, No.2, Summer 1983 - Lucas, Linda (The Southeastern Library Association, 1983)
The Southeastern Librarian, Vol.33, No.02, Summer 1983. Periodical.
1 electronic record. 24 pages. Scanned from original document. Contents Include: Linda Lucas- Editor's Page- 31, Barratt Wilkins- From the President's Desk- 33, SELA Chronicle- 34
Keywords: Periodicals | Southeastern Library Association